Las medidas de amparo contra la violencia a la mujer y a la familia y el derecho a la justicia como equidad de género - Gavidia Orozco, Jaime Ramiro (2015)
The present research on the theme: "The measures of protection against violence to women and the family and the right to justice and gender equality" has developed in its six chapters, which are detailed below: Chapter I, I am talking about the problem, including its problematic, formulation and delimitation, so too has the justification, general objectives and specific, the hypothesis with their variables, dependent and independent, and finally the resources that have been used for embodiment of the present investigation. Chapter II refers to the theoretical framework, which has been collected multiple criteria of national and foreign authors, speaking about violence to women and the family, partner and legal developments regarding the right to justice as gender equity and its current situation, it also includes legislation and jurisprudence. In chapter III, the methodology used in the research is described; the methods used, the types of research, people, samples techniques and instruments used in data collection. Chapter IV contains the analysis and interpretation of results regarding the research hypothesis. Chapter V is the research findings and recommendations. Chapter VI finally contains the proposal, the same as it is structured by a history, rationale, aims and objectives, description and development of the proposal, beneficiaries and social impact.